OPTIMIZING OIL VESSEL TERMINAL LAYOUT: A COMPREHENSIVE LITERATURE REVIEW - Filemon, F; Gumelar, Fajar; Nugroho, Setyo (Journal of Marine-Earth Science and Technology, 2023)
This research paper systematically explores oil vessel terminal layout optimization, emphasizing safety considerations, environmental impact assessment, and efficient infrastructure design. The study employs a comprehensive methodology involving literature review and data synthesis, delving into technical and organizational safety aspects, safety exclusion zones, and the key components comprising an oil vessel terminal layout. By providing a holistic overview and a visual representation of terminal infrastructure, this research contributes to a deeper understanding of the complexities involved, offering valuable insights for industry practitioners and future research endeavours in this domain.